The Theology of Preaching: A Search for the Authentic - Woodfin, Yandall (Scottish journal of theology, 1970)
The creative tension which exists between the preacher's longing to proclaim an authentic Word from God and the need to acknowledge his own human involvement is reflected characteristically in the young Karl Barth. Writing from the pastorate during the early days of his theological struggles, he confessed that on Sunday mornings the preacher